Teknik Penerjemahan Dalam Buku Terjemahan Pengantar Sistem Informasi Perspektif Bisnis dan Manajerial Pendekatan Kelompok Nomina Linguistik Sistemik Fungsional - Nurdin Bramono (Jurnal Multidisiplin Madani, 2022)
This study is qualitative which aims at identifying translation technique in Introduction to Information System that translated into Bahasa Indonesia and the impact its acceptability. The data was sentences, contains of the term of information system. Technique data collection was questionnaire and in dept interview. Meanwhile, technique data analysis was domain analysis, taxonomic analysis, componential analysis and theme analysis. The result showed that highest translation technique used is literal with 24,60% and naturalized borrowing 24% (see table 1). Furthermore, in line with translation technique findings, there was an impact in using this translation technique. The findings show that this book has high acceptability on its translation. As seen in Table II that 77,77% of the data has good acceptability. Hence, it can be said that, the use of literal technique and natural borrowing are appropriate in translating this text, since it will contribute to create good acceptability of specific term in target language, based on the context of the text.